La Infanta Filipina a recreation of the Manila Galleon - Soriano, Emilia C.; Florendo, Raquel Baltazar (1989.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Ocean liners -- Decoration; Ship decoration -- Philippines